Récits de la lutte contre le VIH/sida en Algérie - Amel Zertal; Othmane Bourouba; Adel Zeddam (L’Année du Maghreb)
The history of the fight against HIV/AIDS in Algeria is not well known. Three major actors of this history retrace it in broad strokes. Its emergence followed a political change that made the creation of non-governemental organizations possible. In this context of effervescence, AIDS Algérie and then El Hayet, an organization of people living with HIV, were developed. As soon as antiretroviral treatments appeared, the public authorities made them available free of charge, while the Global Fund financed prevention programs aimed at the most affected groups, although their sustainability is not guaranteed. The emergence of the Covid epidemic has made the implementation of HIV control actions more complex, especially since the lessons learned from the AIDS epidemic have not been applied to the management of the new epidemic.